Security and Trust in EDI - A Qualitative Study of EDI Risks Undertaken in Australia - Ratnasingham, Pauline (Malaysian Journal of Computer Science, 1998)
Electronic commerce presents many opportunities for public and private sectors to capitalise on technologies such as Electronic Data Interchange. EDI allows improvements in business performance and efficiency, in building of new markets and expanding of old ones. However, a significant barrier to the organisational adoption and diffusion of EDI, is the lack of knowledge in the need for adequate security and control. This paper validates the results of a previous survey and presents the findings of seven case studies using EDI systems. The organisations studied represented a crosssection of the industry groups, two from the automotive and telecommunication industries, and one from each of the banking, clothing and petroleum industries. In addition the importance of trust and its influence on the EDI risks are examined and the paper contributes to both the theory and current industrial practice.